Peran Struktur Modal dalam Meningkatkan Nilai Perusahaan : Analisis pada Konteks Keuangan Perusahaan - Susiatin, Emy; Ardiani Ika Sulistyawati; Teti Susilowati (Program Studi Akuntansi - STIE Kesuma Negara Blitar, 2024)
Corporate value is very important for public companies because it shows the performance of the company, which can influence the perception of the company by potential investors and make potential investors funds seeking to invest in the company. A high stock price increases the value of the company and potential investors see the company as good. This study examines the increase in capital gains between 2014 and 2016 as changes in capital structures. Based on the final data, which is the second data analyzed using the SEM program and Smart PLS 1.0, this study concluded that profitability and growth potential have no effect on financial structure. Liquidity affects financial planning. Profitability, growth opportunities and financial structure affect the profitability of the company, Liquidity has no effect on the profitability of the company. Liquidity affects firm profitability indirectly, while capital structure is an intermediate variable.